The discoursal construction of female physical identity in selected works in children's literature - Hunt, Sally Ann (Rhodes University, Faculty of Humanities, Department of English Language and Linguistics, 2011)
This thesis reports on an analysis of the discursive construction of female and male physical identity in children's literature and explicitly combines corpus linguistic methods with a critical discourse approach. Based on three novels from each of the Chronicles of Narnia and the Harry Potter series, it shows clear gendering of body parts, not only in terms of the purely quantitative preferences for certain body parts to be associated with one or other gender, but in terms of discourse prosody, or the uses to which the body parts are put. Human body parts in these series are mostly used in the following four ways, all of which show differences in realisation in terms of gender: · to describe individuals, physically, in order to distinguish one from the other; · to convey emotion, unintentionally as well as consciously; · for physical interaction between people and · for interaction with the world more broadly: responses to danger and agency, i.e. the ability to act on the world and the nature of what is achieved. The use of body parts by characters to express emotion and act agentively on the world is revealed to be strongly gendered in the two series. I characterise the most prominent patterns in terms of the bodily products blood, sweat and tears, of which the last is strongly connected to female characters, who are generally associated with emotion. The other two, referring to active participation in fighting and injury, as well as agency, are almost exclusively reserved for males, with female characters rendered unable to act on the physical world as a result of overwhelming feelings. The females' response to danger suggests stereotyped discourses of inequality which see women and girls as requiring protection and being physically incapable. Thus gender is still a particularly salient aspect in these widely-read examples of children's literature, despite plots which appear to be fairly positive towards women. The strength of the inclusion of a corpus approach in this study lies in its capacity to reveal objective, and often fairly covert, trends in language use. These in turn enrich the critical analysis of discourses in these influential texts, which facilitates social change through linguistic analysis.
Keywords: Rowling, J K -- Criticism and interpretation; Lewis, C S (Clive Staples), 1898-1963 -- Criticism and interpretation; Girls in literature; Girls -- Identity; Human body in literature; Gender identity in literature; Sex role in literature; Children's stories, English -- History and criticism; Young women in literature; Women in literature